Inclusive education: Equality and equity (Teachers’ views about inclusive education in Malaysia’s primary schools) - Salleh, Rosmalily; Woollard, John (Jurnal Pendidikan Bitara UPSI, 2019)
The desire for inclusive education is recognised by many countries, but the practice is inconsistent because of the complexities and variability in implementation. Malaysia has committed to and embarked on the journey towards educational system reform. The pledge to provide quality and inclusive education is emphasised in the 2013-2025 Malaysia Education Blueprint. However, Malaysia’s contexts, including its diverse ethnicity, language, culture, religion, education and school systems, have implications for the implementation and promotion of inclusive education. This study explores and brings to light teachers’ significant yet overlooked views of inclusion and inclusive education at this important juncture of the country’s phase. It aims to bring a better understanding of the promotion of inclusive education in Malaysia’s primary schools, by focusing on the practitioners’ views. The study adopts a qualitative approach that employs descriptive and exploratory methods. Participants are purposely sampled from five national primary schools: three schools with the Special Education Integration Programme (SEIP) and two schools without SEIP. They, 25 teachers (mainstream and special education) including the headteachers, are interviewed individually and 51 participated in eight focus group interviews. The findings are processed through a thematic, inductive approach using qualitative analysis software. This paper argues that teachers view inclusive education as a challenging concept. Such views are influenced by a range of factors such as socio-cultural attitudes towards disability, educational systems, inefficient utilisation of resources, insufficient facilities, and teachers’ lack of knowledge and skills about special education and SEN. The findings will be of value to those responsible for planning and developing the policy and programmes regarding inclusive education, special education, and specifically educational systems in moving towards inclusive systems and schools.